Comparing Open-Book and Closed-Book Examinations: A Systematic Review. (April 2016) - Durning, Steven J.; Dong, Ting; Ratcliffe, Temple; Schuwirth, Lambert; Artino, Anthony R.; Boulet, John R.; Eva, Kevin
Abstract : Purpose: To compare the relative utility of open-book examinations (OBEs) and closed-book examinations (CBEs) given the rapid expansion and accessibility of knowledge. Method: A systematic review of peer-reviewed articles retrieved from MEDLINE, ERIC, Embase, and PsycINFO (through June 2013). In 2013–2014, articles that met inclusion criteria were reviewed by at least two investigators and coded for six outcome categories: (1) examination preparation, (2) test anxiety, (3) exam performance, (4) psychometrics and logistics, (5) testing effects, and (6) public perception. Results: From 4, 192 identified studies, 37 were included. The level of learner and subject studied varied. The frequency of each outcome category was as follows: (1) exam preparation (n = 20; 54%); (2) test anxiety (n = 14; 38%); (3) exam performance (n = 30; 81%); (4) psychometrics and logistics (n = 5; 14%); (5) testing effects (n = 24; 65%); and (6) public perception (n = 5; 14%). Preexamination outcome findings were equivocal, but students may prepare more extensively for CBEs. For during-examination outcomes, examinees appear to take longer to complete OBEs. Studies addressing examination performance favored CBE, particularly when preparation for CBE was greater than for OBE. Postexamination outcomes suggest little difference in testing effects or public perception. Conclusions: Given the data available, there does not appear to be sufficient evidence for exclusively using CBE or OBE. As such, a combined approach could become a more significant part of testing protocols as licensing bodies seek ways to assess competencies other than the maintenance of medical knowledge. Abstract : Supplemental Digital Content is available in the text.